Variability of jump kinetics related to training load in elite female basketball - Legg, J.; Pyne, D. B.; Semple, S.; Ball, N. (Sports, 2017)
The purpose of this study was to quantify changes in jump performance and variability in elite female basketballers. Junior and senior female representative basketball players (n = 10) aged 18 ± 2 years participated in this study. Countermovement jump (CMJ) data was collected with a Gymaware™ optical encoder at pre-, mid-, and post-season time points across 10 weeks. Jump performance was maintained across the course of the full season (from pre to post). Concentric peak velocity, jump height, and dip showed the most stability from pre- to post-season, with the %CV ranging from 5.6-8.9%. In the period of the highest training load (mid-season), the variability of within-subject performance was reduced by approximately 2-4% in all measures except for jump height. Altered jump mechanics through a small (0.26 effect size) increase in dip were evident at mid-season, suggesting that CMJ analysis is useful for coaches to use as an in-season monitoring tool. The highest coefficient of variation (8-22%CV) in inter-set scores in all measures except eccentric peak velocity also occurred mid-season. It appears that in-season load not only impairs jump performance, but also movement variability in basketball players.